2018
DOI: 10.1002/bjs.10804
|View full text |Cite
|
Sign up to set email alerts
|

Operating list composition and surgical performance

Abstract: BackgroundRecent reviews suggest that the way in which surgeons prepare for a procedure (warm up) can affect performance. Operating lists present a natural experiment to explore this phenomenon. The aim was to use a routinely collected large data set on surgical procedures to understand the relationship between case list order and operative performance.MethodTheatre lists involving the 35 procedures performed most frequently by senior surgeons across 38 private hospitals in the UK over 26 months were examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…[34][35][36][37][38][39][40] Interventions that directly target cognitive and motor preparation are showing promise. The benefits of 'warming up' for optimal surgical performance are becoming clearer, [41][42][43] with emerging evidence indicating that the risk of intraoperative errors related in perceptual identification and spatial orientation might be ameliorated by preoperative interaction with virtual and physical visual aids. 44,45 Such interventions are unlikely to work in isolation, however; healthcare delivery is a complex process involving the interactions of dynamical systems and, as such, interventions at the proximal level need to be considered in the context of the system in which they are embedded.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40] Interventions that directly target cognitive and motor preparation are showing promise. The benefits of 'warming up' for optimal surgical performance are becoming clearer, [41][42][43] with emerging evidence indicating that the risk of intraoperative errors related in perceptual identification and spatial orientation might be ameliorated by preoperative interaction with virtual and physical visual aids. 44,45 Such interventions are unlikely to work in isolation, however; healthcare delivery is a complex process involving the interactions of dynamical systems and, as such, interventions at the proximal level need to be considered in the context of the system in which they are embedded.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies and reviews report that the order of the theatre list influences surgical performance. [5][6][7] This includes a significant effect on the operating time, especially on lists where the same procedure is repeated. 5 It has also been suggested that the complexity of the case could be a crucial criterion for list ordering.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] This includes a significant effect on the operating time, especially on lists where the same procedure is repeated. 5 It has also been suggested that the complexity of the case could be a crucial criterion for list ordering. We, therefore, investigated how case complexity influences the order of the list in this survey-based study completed by varying grades of cataract surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a predictable operative duration is crucial for the efficient scheduling of operating room utilization, as both under-and overscheduling have major economic impacts. Among other factors, the team composition plays a relevant role in the operative duration beyond the learning curve [14][15][16][17][18]. To date, the impact of the surgical team composition on the duration of enbloc robot-assisted radical cystectomy and nephro-ureterectomy, a complex, multistep procedure, has not been explored.…”
Section: Introductionmentioning
confidence: 99%